Theology and Ecology in Dialogue: The Wisdom of Laudato Si’ - Harun, Martin (DISKURSUS - JURNAL FILSAFAT DAN TEOLOGI STF DRIYARKARA, 2022)
This is an important book by Dermot A. Lane, widely known as one of the leading theologians in Ireland with a notable international profile; recognized for his work in re-positioning Catholic theology through dialogue with other disciplines, worldviews, and insistent social, cultural and political problems. In this his latest work he explores new roads opened up by Laudato Si’ for contemporary theology; and shows how ecological questions should permeate the whole of theology and Christian faith.